2009
DOI: 10.1007/s10584-009-9700-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the current and future thermal regimes of three streams located in the Wenatchee River basin, Washington State: some implications for regional river basin systems

Abstract: We examine summer temperature patterns in the Wenatchee River and two of its major tributaries Icicle and Nason Creeks, located in the Pacific Northwest region of the United States. Through model simulations we evaluate the cooling effects of mature riparian vegetation corridors along the streams and potential increases due to global warming for the 2020s-2080s time horizons. Site potential shade influences are smaller in the mainstream due to its relatively large size and reduced canopy density in the lower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 19 publications
7
30
0
Order By: Relevance
“…This finding is similar to previous a study that demonstrated T s response to climate change was more related Q reductions than to increased T a (Cristea and Burges 2010). We also demonstrate that T s and subsequent salmonid incubation responses to future climate scenarios are likely to vary with interannual hydroclimatological conditions, with 2010 having a greater magnitude of Q and T s response in all scenarios.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is similar to previous a study that demonstrated T s response to climate change was more related Q reductions than to increased T a (Cristea and Burges 2010). We also demonstrate that T s and subsequent salmonid incubation responses to future climate scenarios are likely to vary with interannual hydroclimatological conditions, with 2010 having a greater magnitude of Q and T s response in all scenarios.…”
Section: Discussionsupporting
confidence: 90%
“…Expected changes include earlier spring snowmelt (Mote et al 2005;Stewart 2009;MacDonald et al 2011), reductions in late season streamflow (St. Jacques et al 2010), increased drought (Pederson et al 2010;Sauchyn and Bonsal 2013), and subsequent increased human demand on water resources (Schindler and Donahue, 2006). Stream thermal regimes are likely to respond to changes in hydroclimatic regimes (Cristea and Burges 2010), as the capacity for streams to store heat is inversely proportional to volume (Poole and Berman 2001;Webb et al 2003). Degradation of thermal habitat as a result of anthropogenic and natural disturbance, coupled with competition from introduced species, will likely further reduce habitat availability for native salmonids in the Rocky Mountains (Meyer et al 1999;Isaak et al 2012a;Isaak et al 2012b;Jones et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Brown, 1969;Sridhar et al, 2004;Cristea and Burges, 2010), were disregarded. Although this contributes to uncertainties in river discharge and water temperature simulations, impacts of processes like groundwater advection, energy exchange between river bed and water interface, dispersion of heat and local conditions (topography and vegetation) in main rivers are relatively small at this large scale (Liu et al, 2005;Caissie, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On large rivers where cold-water storage is available behind reservoirs, water releases could be timed to decrease temperatures during critical biological periods as has been the case on the Clearwater River for migrating salmon in northern Idaho the last two decades. On smaller streams, maintaining or restoring instream flows and improving riparian communities to increase stream shading could offset significant amounts of future warming where degradation is severe (Meier et al 2003;Moore et al 2005;Cristea and Burges 2009). Removal of barriers to fish movement could decrease fragmentation and provide populations the flexibility to shift their distributions and track thermal habitat as needed (Fausch et al 2006;Daufresne and Boet 2007;Isaak et al 2010a).…”
Section: Management Implicationsmentioning
confidence: 99%